SEISMO-IONOSPHERIC DEPRESSION OF THE ULF GEOMAGNETIC FLUCTUATIONS AT KAMCHATKA AND JAPAN - Schekotov A.; Molchanov O.; Fedorov E.; Gladyshev V.A.; Belyaev G.G.; Hattori K.; Chebrov V.; Sinitsin V.; Gordeev E.; Hayakawa M. (My University, 2006)
We study preseismic behavior of the ULF geomagnetic variations at Karymshino (E158.13, N52.83), Russia, and Matsukawa (E140.94, N39.88), Japan. A depression of ULF power around local midnight is registered several days before strong isolated earthquakes. The relative depression, i.e. δ D = (frac(1, G) - 〈 frac(1, G) 〉) / 〈 frac(1, G) 〉 has been analyzed, where the absolute depression is defined as a sum of inversed values of spectral power densities of horizontal components (where frac(1, G) = 1 / Phh and Pdd are the mean spectral densities of H and D components) in a sliding window ±(10-15) days. At Karymshino the most evident effect is found 3 days before an earthquake for the 0.5 h vicinity of local midnight in the frequency range 0.02-0.05 Hz. The data from Matsukawa are used to estimate the spatial scale of the effect and its local nature has been confirmed. Furthermore there is a definite correlation between the depression value and index of seismic activity. Thus, the analysis supports a hypothesis on seismic origin of the observed ULF geomagnetic field depression preceding an earthquake. © 2006.
Keywords: PRE-SEISMIC; SPECTRA; ULF GEOMAGNETIC VARIATIONS